Clockwork Rhetoric : The Language and Style of Steampunk - Brummett, Barry, 1951- (Book collections on Project MUSE., 2014)
"Explores how the aesthetic and cultural movement 'steampunk, ' [an aesthetic style grounded in the Victorian era, in clothing and accoutrements modeled on a heightened and hyper-extended age of steam], persuades audiences and wins new acolytes"--Amazon.com